Nipped in the bud : young Guyanese adults and their functional literacy - Jennings, Zellynne (Education and Development Services Inc. DiamondGY, 1998)
Presents an in-depth study of difference in functional literacy among young Guyanese adults according to age group, highest level of education, gender, environment, race and employment status.